Quality Assurance Studies In Architectural Education - Alptekin, Gamze (Iated-Int Assoc Technology Education A& Development, Lauri Volpi 6, Valenica, Burjassot 46100, Spain, 2013)
Increasing demand for higher education and increase in number of universities constituted a competitive environment in higher education market. Higher education schools and universities forced to improve quality of education, respond to student requirements, increase research studies, improve industry relations and develop projects for the benefit of the society, in order to become a world class university. Quality assurance in higher education is the tool for evaluation of universities according to the first two abovementioned performance criteria, considering the formers. Ranking is another method of evaluation for universities considering research performance, citations, innovation projects and social responsibility projects. This paper will focus on Bologna Process and accreditation as a quality assurance system in higher education in general. Architecture has been a popular, admiring and respectful profession at all times and now with medicine and law, it is seen as one of the three main professions for the future. Consequently architectural education is, as has always been, a popular field of study and many students demand having architectural education. The contradiction, beside the outcomes, between details of the two quality assurance systems - Bologna Process and accreditation in architectural education will be explained in particular.
Keywords: Quality assurance; education quality; architectural education; accreditation; Bologna Process; higher education evaluation; Kalite güvencesi; eğitim kalitesi; mimari eğitim; Bologna Süreci; akreditasyon; yüksek öğretim değerlendirmesi